Influence of contrast compression therapy and water immersion contrast therapy on biomechanical parameters of the forearm muscles in martial arts athletes - Robert Trybulski; Robert Trybulski; Jarosław Muracki; Robert Roczniok; Wacław Kuczmik; Nicola Lovecchio; Adrian Kużdżał (Frontiers in Physiology)
ObjectiveThis study compared the immediate effects of game-ready contrast therapy (GRT) and contrast water immersion therapy (CWT) on stiffness, muscle tone, flexibility, pressure pain threshold, and isometric muscle strength.DesignExperimental, single-blind, randomized controlled trial. Thirty volunteers training MMA (age: 28.20 ± 7.57 years, BMI: 26.35 ± 4.06, training experience: 10.37 ± 7.34) were randomized to two groups: experimental (n = 15) and control (n = 15). In the first phase, the experimental group underwent GRT and the control–game-ready sham therapy (GRS). After a 2-week break, the experimental group underwent CWT and the control–contrast water sham therapy (CWS). The main outcome measures were muscle tone (T) stiffness (S) elasticity (E), pressure pain threshold (PPT), and maximum isometric strength (Fmax) assessed before therapy (Rest) and 5-min and 1-h after treatment (PostTh5min and PostTh1h).ResultsAnalysis of variance results for T, S, E, PPT, and Fmax showed statistically significant differences (p < 0.0001) for main effects and interactions. For both therapies GRT and CWT: T, S, and E were lower 5 min after therapy and 1 h after therapy compared to Rest (interaction effect, p < 0.00001). For both therapies GRT and CWT the PPT and Fmax were higher 5min and 1 h after therapy compared to Rest (interaction effect, p < 0.0001). The post hoc test showed statistically significant differences (p < 0.0001) for T, S, E, PPT, and Fmax in the experimental groups (GRT and CWT) for Rest-PostTh5min and Rest-Post1h. No statistically significant differences were found for Post5mi-Post1h. The effect size of Cohen’s d for S, E, PPT, and Fmax showed similar values, with only T being significantly more pronounced in the GRT group (large, d > 0.8). There were no statistically significant differences (p > 0.05) in the control groups (GRT for GRS and CWT for CWS) in the Rest-PostTh5min-PostTh1h range.ConclusionThe positive impact of both contrast therapy strategies as a stimulus influencing important aspects of biomechanics was confirmed. The results showed similar effects of CWT and GRT (both similarly lowering S and E and increasing Fmax and PPT) except for the analysis of muscle tone, where the lowering effect of GRT had larger effect. These findings can be directly applied by researchers, sports medicine specialists, and martial arts trainers interested in the biomechanical effects of therapy on athletes, improving their understanding and practice.